Manual de procesos y procedimientos para la Agropecuaria BRILOOR S.A ubicada en el cantón Portoviejo - Cedeño Quijije, Carmen Valeria (2021)
This research focuses on developing a manual of processes and procedures in the Agropecuaria BRILOOR SA located in the Portoviejo canton for the improvement of administrative management, for its precise execution three specific phases were developed derived from the main object, in the first instance a diagnosis of the current situation, by means of information gathering methods and techniques such as the interview where the processes that this applies in its management were known, in such a way a survey was used of the 16 employees who work in the Agriculture, allowing to verify the activities and functions they perform; Since with the data obtained we proceeded to the description and detail of the processes and procedures in BRILOOR SA, through a characterization sheet of the same, which helped to visualize all the tasks carried out in the poultry farm and thus determine the points of greater importance in the map and process diagram, once the incidents were identified where it was perceived that the tasks were not defined in the company or the responsibilities were delegated, the process manual was prepared in Agropecuaria BRILOOR SA, which will contribute to the management administrative and operational, thus concluding that by contrasting this information, it was possible to propose a precise delineation of the processes that are carried out in the poultry farm, with the purpose that the activities are carried out effectively and efficiently, thus promoting growth and stability of BRILOOR SA